Measurements and modeling of long-path 12CH4 spectra in the 5300–5550 cm−1 region. (November 2017) - Nikitin, A.V.; Thomas, X.; Daumont, L.; Rey, M.; Sung, K.; Toon, G.C.; Smith, M.A.H.; Mantz, A.W.; Tashkun, S.A.; Tyuterev, Vl.G.
Highlights: 5934 line positions and intensities were retrieved in the 5300–5550 cm −1 region. 12 CH4 line list with assignments was made in the 5300–5550 cm −1 region. 2847 experimental line positions were modeled to 0.0025 cm −1 . 2227 experimental line intensities at 296 K were modeled to 8.6% rms . Abstract: A new study of 12 CH4 line positions and intensities was performed for part of the Tetradecad region between 5300 and 5550 cm −1 using four long path (202 m, 602 m, 1604 m and 1804 m) spectra of normal samples of CH4 at different pressures recorded with a Fourier transform spectrometer in Reims, France. Line positions and intensities were retrieved by least square curve-fitting procedures and analyzed using the effective Hamiltonian and the effective dipole moment expressed in terms of irreducible tensor operators adapted to spherical top molecules. An 80 K spectrum from JPL of enriched 12 CH4 was used for low-J line positions. One other 80 K spectrum from JPL of enriched 13 CH4 was used to discern the isotopic lines. A new measured linelist contains positions and intensities for 5934 features. Quantum assignments were made for 2847 transitions, which represent ∼90% of the integrated line intensity observed in this region. All assigned line positions and 2227 selected line intensities were fitted with RMS standard deviations of 0.0025 cm −1 and 8.6%, respectively. The sum of observed intensities between 5300 and 5550 cm −1 fell within 2% of the predicted value from ab initio variational calculations.